Predictors of Patient Satisfaction in Hand and Upper Extremity Clinics - Shaterian, Ashkaun; Sayadi, Lohrasb Ross; Santos, Pauline F. Joy; Krasnoff, Chloe; Evans, Gregory R. D.; Leis, Amber R. (Journal of Hand and Microsurgery, 2019)
Introduction Patient satisfaction is an important clinical marker for hand/upper extremity patients. Few studies have investigated the predictors of patient satisfaction in the clinic setting. Our objective was to analyze patient satisfaction surveys to explore factors that influence patient satisfaction.Materials and Methods We conducted a retrospective analysis assessing patient satisfaction in the hand/upper extremity clinics at our university medical center between 2012 and 2018. Patient satisfaction was assessed via Press Ganey Hospital Consumer Assessment of Healthcare Providers and Systems surveys. Patient demographics, satisfaction scores, and clinic experience questionnaire responses were evaluated. Statistical analysis was conducted to identify significant trends.Results Between 2012 and 2018, 102 surveys were completed. Scores ranged from 5 to 10 with an average provider rating of 9.56. We found six factors significantly influenced patient satisfaction: adequate time was spent with the provider, provider showed respect, patient was seen by provider within 15 minutes of appointment time, provider listened sufficiently, patient received understandable medical instructions, and understandable medical explanations (p < 0.05).Conclusion Achieving patient satisfaction is an important clinical marker in hand/upper extremity clinics. Patient satisfaction has defined predictors wherein various clinical factors can influence patient satisfaction and willingness to refer their provider to other patients.
Keywords: hand; upper extremity; patient satisfaction